(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
In this conversation, Tatiana Cobbett shares how her artistic career was built, marked by the interweaving of different artistic languages: dance, music, and theater. She also explains how the idea of ​​creating a show exclusively with women emerged in the 1980s and how she developed the various activities that encompass artistic work, from production to performance "perpetual crochet" that involves sustainability, partnerships, and collaboration. She also discusses her involvement in struggles and initiatives to expand access to culture for all, to guarantee dignity for artists, and to encourage original works, especially those created by women.